2013
DOI: 10.1016/j.amepre.2013.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Taxicab Security Equipment in Reducing Driver Homicide Rates

Abstract: Background Taxicab drivers historically have had one of the highest work-related homicide rates of any occupation. In 2010 the taxicab driver homicide rate was 7.4 per 100,000 drivers, compared to the overall rate of 0.37 per 100,000 workers. Purpose Evaluate the effectiveness of taxicab security cameras and partitions on citywide taxicab driver homicide rates. Methods Taxicab driver homicide rates were compared in 26 major cities in the U.S. licensing taxicabs with security cameras (n=8); bullet-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Our findings suggest cities where taxicabs are equipped with cameras could result in fewer taxicab driver homicides particularly in cities with an ordinance mandating taxicabs are equipped with cameras. Furthermore, these findings are consistent with a previous analysis examining news clippings to identify homicides (Chaumont Menéndez et al 2013). Specifically, results of the news clippings analysis were concordant with the current study with respect to an observed effect of cameras in possibly reducing citywide taxicab driver homicide rates, but inconclusive for the effect of partitions.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings suggest cities where taxicabs are equipped with cameras could result in fewer taxicab driver homicides particularly in cities with an ordinance mandating taxicabs are equipped with cameras. Furthermore, these findings are consistent with a previous analysis examining news clippings to identify homicides (Chaumont Menéndez et al 2013). Specifically, results of the news clippings analysis were concordant with the current study with respect to an observed effect of cameras in possibly reducing citywide taxicab driver homicide rates, but inconclusive for the effect of partitions.…”
Section: Discussionsupporting
confidence: 91%
“…Cameras and partitions, two major types of safety equipment, were found to be distributed in geographically different regions among the largest US cities. 10,11 Generally, cameras were found to be mandated by city ordinance in the West and company policy in the South while partitions were primarily mandated in the Northeast and Midwest. 10,11 Of further concern is this uneven distribution of two key types of recommended safety measures.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Generally, cameras were found to be mandated by city ordinance in the West and company policy in the South while partitions were primarily mandated in the Northeast and Midwest. 10,11 Of further concern is this uneven distribution of two key types of recommended safety measures. There is no current information available at the national level that identifies implementation of the recommended safety measures at the driver/car level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at a fifteen-year span from 1996 to 2010, it was determined that there was no difference in the homicide rates in cities that had the bullet-proof partitions versus those that did not. However, there was a substantial reduction, almost four times lower rate, in homicides in cities that has cameras installed in their taxicabs (Menendez et al, 2013). This does not indicate that taxicabs should not have the bullet-proof shields; it merely means that research has not indicated that they are effective in reducing homicides or attempted homicides.…”
Section: Cameras and Dash-cams That Have The Ability To Record What Imentioning
confidence: 99%